ASSESSING THE ACQUISITION OF CLAUSE CONNECTORS BY THE FIRST SEMESTER STUDENTS OF STMIK PRIMAKARA IN ACADEMIC YEAR 2019/2020 - Eka Grana Aristyana Dewi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
The aim of this study is on evaluating the ability of students of STMIK Primakara in the academic year 2019/2020 in mastering clause connectors. The norm-referenced measures of five standard values were used to analyze the data. The students were 187 students who have heterogeneous characteristics as the population. In taking the sample, quota random sampling technique was used. There were 30 students determined as the sample of the study by using quota random sampling technique. The data analysis result showed that: (1) 6.67% had excellent ability; (2) 30.00% had good ability; (3) 13.33% had sufficient ability; (4) 46.67% s had insufficient ability, (5) 3.33% had poor ability in mastering clause connectors. If the outcome of the study were applied as the basis for the sample’s degrees, then there was 50.00% who failed in learning and acquiring clause connectors, and the rest 50.00% was good enough in learning and acquiring clause connectors. It meant that the acquisition of clause connectors by the students was sufficient. The data of the study conducted was considered to have fairly amount of validity and reliability, as there were many factors that could interfere the conclusions. The result of the study conducted can help to improve planning for teaching specifically in understanding clause connectors.